Do Magnetically Controlled Growing Rods Stimulate Longitudinal Vertebral Growth in Early-Onset Scoliosis Patients? - BEZER, MURAT (ELSEVIER SCIENCE INC, 2020)
OBJECTIVE: Distraction-based systems are the most common systems used in the treatment of early-onset scoliosis. In addition to its corrective and deformity progression preventive properties, its vertebral growth stimulation effect has been proved. Recently popularized magnetically controlled growing rods (MCGRs) showed superior results in terms of outcomes and decreased complication rate. Its vertebral growth stimulation effect has not been studied. The aim of the study is to evaluate the vertebral growth stimulation effect in patients treated with MCGR. METHODS: Patients with progressive scoliosis treated by dual MCGR, who had no obvious lumbar vertebral deformity and had a regular 3-month interval spinal lengthening for at least 30 months, were subdivided into 2 groups according to the inclusion of L3 vertebra within instrumentation segments. The L3 vertebral vertical and horizontal lengths were measured postoperatively and at the last follow-up, and their differences were analyzed statistically in both groups. RESULTS: Twenty-four patients were included; 18 of them had an L3 vertebra outside instrumentation segments, while the other 6 had spanned by MCGR. Uninstrumented L3 were followed up for an average of 36 months. The height difference between initial postoperative examination and the last follow-up was 3.55 mm +/- 0.63 mm, and the width difference was 3.85 mm +/- 0.75 mm. Conversely, patients with instrumented L3 were followed up for a mean of 38.9 months. Their initial postoperative examination and last follow-up differences in height and width were 6.91 mm +/- 1.11 mm and 3.66 mm +/- 0.92 mm, respectively. CONCLUSIONS: Frequent distractions stimulate longitudinal vertebral growth in vertebrae spanned by MCGR.
Keywords: Distraction; Early-onset scoliosis; Longitudinal vertebral growth; Magnetically controlled growing rod; SPINAL INSTRUMENTATION; BODY GROWTH; FUSION